The Mystery of the World in the Liturgy - Bogusław Nadolski (Nicolaus Copernicus University in Toruń, 2011)
In the article The Mystery of the World in the Liturgy attention is directed toward the understanding of the world in the texts of the third edition of the Roman Missal, which deserve consideration due to the clear aggiornamento of relations of the Church to the world, in the direction of sharing all the joys, but also the cares of the world. The world (mundus) is understood as being dynamic, as the whole of living people and things, people burdened by weaknesses, as the place of the lives of people and of common relations which constitute the personality of every man. 'The course' of the world takes place in the glow of God's love. The very seldom appearing contemptio mundi is understood as a poor grade of the worldly life, the intelligent estimate of worldly successes. The most fitting reply for the gift of the world is in giving witness to faith and love, progressing with Christ in daily life. In prayers one should not search for concrete social-political propositions.